Pengaruh Probiotik Dalam Sistem Budidaya Ikan Berkelanjutan: Sebuah Pendekatan Berbasis Kajian Pustaka - Zega, Asokhiwa; Laoli, Destriman; Zebua, Ratna Dewi; Telaumbanua, Betzy Victor; Dawolo, Januari; Zebua, Okniel (Jurnal Perikanan dan Kelautan, 2024)
This study aims to analyze the role of probiotics in supporting the sustainability of fish farming systems. The study was conducted using a literature analysis method from various scientific sources, including journals, academic books, and other scientific works. Probiotics are proven to have significant benefits in increasing feed efficiency, improving water quality, and increasing fish resistance to disease. The study results show that probiotics can reduce ammonia levels by 40%, increase feed conversion efficiency (FCR) by 25%, and increase fish survival rates by 90%. In addition, the use of probiotics can reduce dependence on antibiotics and chemicals, making it more environmentally friendly. The conclusion of this study is that probiotics are an effective solution to improve production efficiency while maintaining environmental sustainability in fish farming. However, further research is needed to optimize the type and application of probiotics that suit various aquaculture systems.